The Implementation of Breastfeeding Counseling on Expectant Mother in Tangerang 2018 - Ikhlasiah, Martia; Winarni, Lastri Mei (International Conference on Sustainable Health Promotion, 2018)
The practice on exclusive breastfeeding for the early birth baby has become a crucial moment which will determine the success of further exclusive breastfeeding. There are some barriers during the old breastfeeding. According to Riskedas (2010) exclusive breastfeeding is ‘the practice of breastfeeding since the delivery of a baby without feeding on other food and drinks during the first 24 hours of life (only breastfeeding, excluding the other food and beverages). Based on Nutritional Status in 2017 by Public Health Director General, Indonesian Ministry of Health 2018 the number of babies that achieve breastfeeding during the first five months is about 46.74%, while the number of babies that complete breastfeeding during the first six months decreases to 35.73%. Those numbers have fallen behind the name that targeted by WHO (90%). The benefits of breastfeeding itself have been discussed by many sources and literature. One of the barriers of exclusive breastfeeding is the lack of information about the importance of the practice on exclusive breastfeeding. The availability of a breastfeeding counselor at the healthcare facility also affects the success rate of breastfeeding. FTKP in JKN era nowadays has become the advanced healthcare tools that face the public directly. Hopefully, with the existence of FTKP could give a real contribution in increasing the number of the Scope of Exclusive Breastfeeding in Tangerang. The purpose of this research is to find the effect of intensive counseling that has been given to third-trimester expectant mothers on the success rate during the first three days postpartum at Azzahra Sitanala Clinic, Tangerang. This research implements the quasi-experiment research design. Sample collection is done by purposive sampling non-equivalent control group technique with inclusion and exclusion criteria which has been defined. The statistical test is done by t-test and Pearson Correlation. The findings of this research are the correlation between intensive breastfeeding counseling with the success rate on three days postpartum.